2004
DOI: 10.2165/00044011-200424030-00004
|View full text |Cite
|
Sign up to set email alerts
|

Depression during Pregnancy

Abstract: Depression during pregnancy is common, affecting an estimated 20% of women. However, conflicting data exist concerning the outcomes of this disorder. Thus, we reviewed studies that presented evidence for the use of antidepressants and those that examined untreated depression during the gestational period, in terms of clinical and epidemiological aspects.Observational studies have provided reassuring evidence of the safety of antidepressant use during pregnancy. However, due to the reluctance of healthcare prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(41 citation statements)
references
References 163 publications
2
34
1
4
Order By: Relevance
“…Even though in the current analysis, the prevalence of maternal depressive symptoms during pregnancy was not stratified by trimesters due to a lack of depression measures at visits subsequent to the first antenatal visit, previous studies have suggested that the prevalence of maternal depression during pregnancy can vary across trimesters [58, 65]. The highest prevalence of clinical depression has been reported in the first and third trimester of pregnancy [66, 67].…”
Section: Discussionmentioning
confidence: 86%
“…Even though in the current analysis, the prevalence of maternal depressive symptoms during pregnancy was not stratified by trimesters due to a lack of depression measures at visits subsequent to the first antenatal visit, previous studies have suggested that the prevalence of maternal depression during pregnancy can vary across trimesters [58, 65]. The highest prevalence of clinical depression has been reported in the first and third trimester of pregnancy [66, 67].…”
Section: Discussionmentioning
confidence: 86%
“…Given the paucity of research evaluating the comparability of two suicidal ideation items from the PHQ-9 and EPDS during pregnancy and a growing body of evidence documenting antepartum depression as one of the major causes of morbidity in low- and middle-income countries (Bennett et al 2004; Ferrari et al 2013), we conducted the present study to examine the concordance of the two suicidal ideation items among pregnant Peruvian women. Considering the lack of updated information among this population, the prevalence of suicidal ideation was assessed using the PHQ-9 and the EPDS.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is a great deal of evidence for the efficacy of both antidepressant medication and psychological interventions for depression (see Joffe, Sokolov, & Streiner, 1996 and Cuijpers, van Straten, Andersson, & van Oppen, 2008 for meta-analyses of the efficacy of antidepressant medication and psychotherapy for depression, respectively), concerns unique to the perinatal period may influence the efficacy of these treatments for this population (Kim, O'Reardon, & Epperson, 2010). For example, in an attempt to limit fetal exposure, antidepressants may be prescribed below therapeutic dosage levels (Bennett, Einarson, Taddio, Koren, & Einarson, 2004a). This problem is complicated further by the fact that most women actually require higher doses of antidepressant medication during pregnancy (Dawes & Chowienczyk, 2001; Hostetter, Stowe, Strader, McLaughlin, & Llewellyn, 2000; Wisner, Perel, & Wheeler, 1993).…”
mentioning
confidence: 99%